Integrating Sharia Values ​​in the Marketing Strategy of Sharia Banks in Indonesia - Rivanda, Alfina Rosy (Maliki Interdisciplinary Journal, 2024)
This study explores the integration of Sharia values into the marketing strategies of Islamic banks in Indonesia and the challenges encountered. Although Islamic banking has shown significant growth, challenges such as low financial literacy and limited product innovation remain obstacles. Effective Sharia marketing strategies require improved education, enhanced human resources, and competitive product innovation. These findings provide insights for Islamic banks in enhancing their competitiveness and adherence to Sharia principles.